The archetypal fable : an inquiry into the function of traditional symbolism in the poetry of Edwin Muir - Gillmer, J E (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1970)
Edwin Muir's poetic vision is bound up with that belief in a twofold structure of reality that in European culture has been called Platonist but which is so ancient and widespread that no one can determine its origins. Though no longer fashionable in a time when materialist philosophies flourish and even Christian clerics are busy "de-mythologizing" their faith, it has been the potent source of our greatest poetry and perhaps, as Kathleen Raine believes, of all true poetry. Those who hold this conviction regard the sensible world as the reflection of an "intelligible" or spiritual world which gives meaning and purpose to life, and they see the objects of nature as images that evoke the ideal forms of a divine reality. For poets, as for traditional men, this belief is less a metaphysic than an intuitive way of apprehending and ordering experience, a "learning of the imagination" inherited from ancient and mysterious sources. To Muir it came directly and spontaneously in the symbolic images of dreams, and the fact that he entitled the first version of his autobiography The Story and the Fable testifies to the importance, both for his life and his poetry, of his belief in two corresponding orders of experience. Intro., p. 1-2.
Keywords: Muir, Edwin, 1887-1959 -- Criticism and interpretation